Reduction, supervenience, emergence and naturalistic truth: reductionism, holism and the description of human nature - Castrodeza, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Methodological reduction is often wrongly identified with ontological reduction. For anyontology has always existential problems of its own which are absent in a methodological approach. Emergence would also be problematic unless it is also contemplated methodologically. As anyphilosophical issue, the question of emergence-reduction is used from a naturalistic stance as aplatform to promote personal ideals of survival. For example, Richard Dawkins would promote aDarwinially reduced world. On the contrary, Richard Lewontin for one would implement a holisticworld essentially Kropotkian. In this context, a contentious term is that of replicator. But this termneed not be either as reductive as Dawkins would have us believe nor as useless as Lewontin thinks.For again evolution by natural selection would always be defended naturalistically along one’s ownideological tenets.